Aspek Hukum Surat Tanda Nomor Kendaraan Yang Pajaknya Telah Habis Masa Berlaku Saat Dilakukan Pemeriksaan Oleh Polisi Lalu Lintas - Abrahamsz, Patricia Julia (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2023)
Introduction: The ticket is a fine imposed by the police on road users who violate the regulation. Vehicle registration certificate or STNK for short, is proof of registration and ratification of a motorized vehicle based on its registered identity and ownership. Motor Vehicle Tax is a tax levied on ownership and/or ownership of motorized vehicles. Purposes of the Research: The traffic police have the authority to provide evidence of violations (tickets) in the form of confiscating vehicle registration certificates during motor vehicle inspections. What legal policy is followed by motor vehicle users whose Vehicle Registration Certificate has expired. Methods of the Research: This study clearly includes normative legal with secondary data. The main problem in this study obviously is achieved by using a juridical-normative approach. Results Originality of the Research: The results of this study were the police have the authority in terms of traffic violations such as vehicle registration tickets whose taxes have expired. All regulations regarding vehicle registration tickets by the police are regulated in the Traffic and Road Transport Law, Law no. 2 of 2002 concerning the Indonesian National Police and Government Regulation No. 80 of 2012 concerning Procedures for Inspection of Motorized Vehicles on the Road and Enforcement of Traffic and Road Transportation Violations. Legal policies that can be carried out include preventive measures that carry out traffic regulation, conduct traffic control, socialize to the public to comply with traffic regulations, increase the number of police facilities and increase patrol escort activities, especially in vulnerable and vulnerable areas. Meanwhile, for repressive efforts, namely by issuing ticket and reprimand.